2007
DOI: 10.1038/sj.sc.3102129
|View full text |Cite
|
Sign up to set email alerts
|

A review of scales for assessing the risk of developing a pressure ulcer in individuals with SCI

Abstract: Background: Pressure ulcers are a common secondary condition that occur post-spinal cord injury (SCI). These ulcers come at tremendous personal and societal cost. There are a number of scales that can be used to identify those who are at risk. Objectives: This review critically evaluates risk assessment scales designed for identifying and predicting skin ulcers. Specifically, studies on the psychometric properties and utility for individuals with SCI were assessed. Methods: The MedLine, CINHAL, Embase, HaPI, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 30 publications
0
38
0
1
Order By: Relevance
“…The BRDs cover only part of these risk factors and is thus considered to be inadequate in the full risk assessment. Risk assessment scales that contain the other parameters and that are more suitable for the patients of our country are required, or the existing scales need serious modifications (29,31,(44)(45)(46)(47)(48)(49). Pressure ulcer development risk in patients treated in ICUs should be revised in coordination with healthcare workers.…”
Section: Resultsmentioning
confidence: 99%
“…The BRDs cover only part of these risk factors and is thus considered to be inadequate in the full risk assessment. Risk assessment scales that contain the other parameters and that are more suitable for the patients of our country are required, or the existing scales need serious modifications (29,31,(44)(45)(46)(47)(48)(49). Pressure ulcer development risk in patients treated in ICUs should be revised in coordination with healthcare workers.…”
Section: Resultsmentioning
confidence: 99%
“…Since their original publication, the metrological values of these two scales have not been sufficiently tested to set clinical practice recommendations. 13 Furthermore, an independent study reports no significant differences between SCIPUS-A, Braden, Norton and Waterlow scales for acute SCI. 14 Since then, new epidemiological studies focusing on patients with SCI have brought up new additional risk factors 15 that can probably explain the lack of validity…”
Section: Introductionmentioning
confidence: 97%
“…9 The predictive value of these scales is, however, unclear. 10 A recent review found no studies on risk factors for pressure ulcers during the initial rehabilitation phase in a homogeneous SCI population. 11 Two rehabilitation studies were identified in this review, but both studies included patients in initial rehabilitation as well as re-hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%